Towards a radical life. The social and aesthetic themes in Helen Keller’s activity in defence of humanity - NIEDUZIAK, EDYTA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Edyta Nieduziak, Towards a radical life. The social and aesthetic themes in Helen Keller’s activity in defence of humanity. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 229-254. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.10 The article is an attempt to describe three biographical motifs of H. Keller, referring to aesthetic experiences (R. Ingarden) caused by various experiences: tactile in contact with sculpture, haptic in contact with music, and literary. The starting point to consider, however, is the category of humanity in the sense of M.S. Archer. The reflexivity characteristic of humanity, combined with the aesthetic experience, makes the themes describe the non-aesthetic experiences of H. Keller. In the analysis, the author used H. Keller’s correspondence, her works, biographical sources, photographs and video recordings.